DIGITAL ETHNOGRAPHY AND THE TRANSFORMATION OF BATE RANUP IN THE MEU UROH TRADITION OF THE UJONG DRIEN VILLAGE - Sapitri, Cut Adira; Maisyura; Mailyza, Risky; Sopar (Puteri Hijau : Jurnal Pendidikan Sejarah, 2025)
The Bate Ranup tradition in the Meu Uroh ceremony is an important part of Acehnese culture that reflects values of respect, social responsibility, and family ties. Bate Ranup consists of betel leaves, areca nut, lime, gambir, and other complementary items arranged in a traditional container, used to invite and honor guests during various customary ceremonies, especially weddings. However, with the advent of the digital era and modernization, the values and functions of Bate Ranup are beginning to shift. The younger generation tends to view this tradition as a relic of the past, and both physical and digital invitations are now preferred for reasons of efficiency and practicality. This study was conducted in Gampong Ujong Drien, West Aceh, using a qualitative approach through digital ethnography. The techniques employed include interviews, observations, and documentation. The research results show that although the use of Bate Ranup is declining, its symbolic meaning remains alive in a society that is aware of the importance of preserving customs. This study emphasizes that the preservation of local culture in the digital era requires an adaptive and collaborative approach across generations so that the noble values embodied in symbols like Bate Ranup remain enduring and relevant today and in the future.